Response of Probiotics and Yeast Added in Different Doses to Rations of Anatolian Merino Lambs on Fattening Performance, Meat Quality, Duodenum and Rumen Histology - Tekce, Emre; Bayraktar, Bulent; Aksakal, Vecihi; Dertli, Enes; Kamiloglu, Aybike; Karaalp, Musa; Gul, Mehmet (Kafkas Univ, Veteriner Fakultesi Dergisi, 2021)
This study investigated the effects of dietary probiotics (Lactobacillus reuteri E81 [LRE], Lactobacillus rhamnosus GG [LRG]), yeast (Saccharomyces cerevisiae S81 [SCSI), and their combined supplementation on fattening performance (BW, DWG, Fl, and FCR), meat quality, and rumen and duodenum histology in lambs. The study material comprised ninety 2.5-month-old Anatolian Merino lambs, and the trial was conducted for 70 days. Nine trial groups, each composed of 10 animals, were established. This study demonstrated that, when compared to the control group, the best fattening performance was achieved in the lambs that received 600 ppm of dietary LRE. Neither visceral organ weights nor rumen and duodenum histology was affected in the groups that received the tested feed supplements. Of the meat colour parameters investigated, the L* value was observed to have increased in the groups that were given feed supplements, excluding Groups LRE-600 and SCS-300. It was determined that the probiotic supplements had no effect on the a* and b* colour parameters, but affected the meat pH value. In conclusion, the assessment of the effects of different doses of dietary probiotics, yeast, and probiotic-yeast combinations on performance parameters, visceral organ weights, and meat quality in Anatolian Merino lambs showed that the best results were achieved in the group that received 600 ppm of LRE alone.
Z anadolu merinos kuzularının rasyonlarına farklı dozlarda ilave edilen probiyotiklerin ve mayanın besi performansı, et kalitesi, rumen ve duodenum üzerine yanıtı
Keywords: Probiotic; Yeast supplementation; Anatolian Merino lamb performance; Feed additive; Meat quality; Histology